2020
DOI: 10.3389/fnhum.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation of the Medial Prefrontal Cortex Has No Specific Effect on Self-referential Processes

Abstract: The processing of self-referential information can be influenced by transcranial magnetic stimulation (TMS). The present randomized controlled study investigated whether similar effects can be elicited through the application of transcranial direct current stimulation (tDCS) regarding the "self-serving bias" (SSB) and the "mnemic neglect effect" (MNE). Seventy-five healthy males (M age = 25; SD = 4.3) were investigated in a betweengroups design with random assignment by applying anodal, cathodal, or sham tDCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Moreover, Dedoncker et al (2019) found that the reduction in negative self-evaluation was associated with reduced functional connectivity between the DLPFC and the left posterior insula. In contrast, the only study targeting the MPFC found no effect of offline tDCS on positive or negative self-evaluation (Mainz et al, 2020).…”
Section: Tdcs Studiesmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, Dedoncker et al (2019) found that the reduction in negative self-evaluation was associated with reduced functional connectivity between the DLPFC and the left posterior insula. In contrast, the only study targeting the MPFC found no effect of offline tDCS on positive or negative self-evaluation (Mainz et al, 2020).…”
Section: Tdcs Studiesmentioning
confidence: 82%
“…Importantly, three studies found that rTMS or anodal tDCS over the MPFC or the DLPFC also reduced negative self-evaluation (self-criticism), suggesting that activation of the prefrontal neurons could have resulted in an overall dampening of emotional response to V-SRP (De Raedt et al, 2017;Dedoncker et al, 2019;De Pisapia et al, 2019). However, Schäfer and Frings (2019) failed to find an effect of anodal VMPFC with cathodal DLPFC tDCS on neutral Mainz et al (2020) failed to find an effect of anodal MPFC with cathodal parietal cortex tDCS on emotional SRP. Considering the V-SRP studies together, a pattern of functional segregation seems to emerge between the left IPL and the MPFC.…”
Section: Verbal Srp (V-srp)mentioning
confidence: 99%
“…Only recently have researchers started investigating the influence of tDCS on the self-reference effect in memory. Interestingly, these past studies show tDCS does not increase the magnitude of the self-reference effect in memory (Mainz et al, 2020;Martin et al, 2019). It is worth noting however, that this past work has focused on item memory (e.g., Mainz et al, 2020), and thus it is less known the extent that selfreference context memory effects might be influenced under active versus sham stimulation.…”
mentioning
confidence: 92%
“…Interestingly, these past studies show tDCS does not increase the magnitude of the self-reference effect in memory (Mainz et al, 2020;Martin et al, 2019). It is worth noting however, that this past work has focused on item memory (e.g., Mainz et al, 2020), and thus it is less known the extent that selfreference context memory effects might be influenced under active versus sham stimulation. Thus, in this investigation we examine the influence of tDCS on self-reference context memory effects.…”
mentioning
confidence: 92%
See 1 more Smart Citation